SECONDARY METABOLITE COMPOUNDS OF FRESHWATER MUSSEL (Pilsbryoconchasp.) FROM SUNGAI PAKU WATERS - Yasti Sari; Syahrul Syahrul; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aims to determine the content of secondary metabolites compounds in freshwater mussel from Sungai Paku waters. The research method used was experimental by extracting the secondary metabolites compounds of freshwater mussel using methanol as a solvent. The research data were analyzed descriptively. The test parameters were yield and analysis of secondary metabolites (alkaloids, steroids, flavonoids, saponins, and phenolics). From this research, it shows that the yield of freshwater mussel with methanol extractionwas 1.29% with the content of secondary metabolites compounds was alkaloid (strong), flavonoids (moderate), and steroids (weak).Keywords: freshwater mussel, secondary metabolites, methanol.